(untitled) (Journal of Atomic and Molecular Sciences, 2015)
Based on first-principles calculations, the electrode force acted on 2,5-dimercapto-pyridazin molecular device is studied. The pressing effects of CO and H_2O molecules on the 2,5-dimercapto-pyridazin molecular junctions are also studied at B3LYP level to simulate the effects of little ambient molecules on the functional molecular junctions. The electronic transport properties of 2,5-dimercapto-pyridazin molecular junction with the pressing of CO and H_2O molecules are studied by employing elastic scattering Green's function method. The numerical results show that the 2,5-dimercapto-pyridazin can be squeezed out of the electrode gap when the electrode distance is compressed to 1.02 nm. It needs about 1.5 nN stretching force to break down the 2,5-dimercapto-pyridazin molecular junction, which agrees with the experiment probes very well. The 2,5-dimercapto-pyridazin molecule is bent by the pressing of CO or H_2O molecule, and is pushed to the edge of Au (111) triangles with the terminal S atoms first to the bridge and then to the top positions of Au (111) triangles, until at last one terminal S atom is pushed out of Au (111) triangle. The pressing of CO and H_2O molecules to the molecular junctions will enhance the couplings between molecule and electrodes, which further enhances nonresonant transmission of the molecular junctions.